Unusal canal configuration in maxillary and mandibular second molars - Ramachandran Ragunathan; A V Rajesh Ebenezar; Ajit George Mohan; S Anand (Wolters Kluwer Medknow Publications, 2016)
This clinical article describes three different case reports of maxillary and mandibular second molars with the unusual anatomy of single root with a single canal and their endodontic management. An unusual case of bilateralism is observed in the first two cases in the form of single-rooted second mandibular molars in both the quadrant of the same patient. The presence of maxillary second molar with single root and single canal in the third case is unusual.